COMMUNITY SERVICE MIDWIFERY CARE PRACTICE SMART COMMUNITY FOR THE ELDERLY IS CHOLESTEROL-FREE WITH ORANGE WATERMELON JUICE AND CHOLESTEROL MASSAGE - Silavati, Vivi; Mujayanti, Rini; Ratnasari, Sitra; Baitul H, Isnul; Jannatunnisa, Linda; Johara, Johara; Nursifa, Mia; Umra, Salsabila (International Journal of Engagement and Empowerment (IJE2), 2024)
Cholesterol is an essential fat for mammalian cells, and its homeostasis is regulated. About 90% of the free cholesterol in cells is found in the plasma membrane. When cholesterol levels are excessive in the blood, cholesterol can accumulate as plaque on the artery walls, contributing to atherosclerosis. There are two types of cholesterol, namely HDL (High-Density Lipid) and LDL (Low-density Lipid). HDL cholesterol is needed by the body to protect against heart disease. On the other hand, the LDL cholesterol content should be lower because LDL can settle in the blood. After all, LDL can settle in the blood if the content is too high. Cholesterol can be prevented with juice and watermelon because there are two compounds, citrulline, and pectin, which can inhibit cholesterol biosynthesis and citrus fruits. After all, limes contain flavonoids, especially hesperidin. Flavonoids play a role in lowering LDL cholesterol and triglyceride levels in the blood, increasing HDL cholesterol, and preventing atherosclerosis. In addition, to reduce cholesterol levels, complementary obstetric care can be carried out through cholesterol massage, emphasizing the ST36 point for 3-5 minutes. The community midwifery practice carried out this time is located at TPMB Bdn Rini Mujayanti, S.Keb Jl. Masjid Al Akhyar RT 29/2 Gandul Cinere Depok. The target of this Community Midwifery Care is the elderly who have high cholesterol, as many as 18 people with high cholesterol ≥200, based on the results of examinations from July to October